The fibre broadband housing premium across three US States - Brian Whitacre (Regional Studies, Regional Science)
This paper meshes 1.7 million housing transactions across three US states (Iowa, Minnesota and Texas) between 2015 and 2021 with data on broadband infrastructure to evaluate the impact of fibre broadband availability on home prices. This was a period of dramatic fibre growth in these states: prior to 2019, fibre was only available to roughly 24% of the houses sold but rose to 54% in later years. A traditional hedonic pricing model that includes a wide array of housing characteristics and census block group-level fixed effects estimates the fibre premium at around 1% in all three states for the full 2105–2021 period. The fibre premium was higher in the earlier part of this period, likely reflecting its novelty during that time. A more rigorous instrumental variable approach estimates the fibre premium at 2% in Minnesota and 9% in Texas. A conservative national estimate of the increase in housing value from deploying ubiquitous fibre is $36 billion.